The impact of tertiary lymphoid structure on the efficacy of postoperative adjuvant transcatheter arterial chemoembolization in patients with hepatocellular carcinoma - Fansheng MENG; Haokang YANG; Biwei YANG (Zhongguo Linchuang Yixue)
ObjectiveTo explore the impact of tertiary lymphoid structure (TLS) on the efficacy of adjuvant transcatheter arterial chemoembolization (TACE) following curative resection in patients with hepatocellular carcinoma (HCC). MethodsA retrospective study enrolled 200 patients receiving adjuvant TACE and 145 non-TACE controls who underwent curative resection for HCC at the Department of Hepatobiliary Surgery, Zhongshan Hospital, Fudan University from January 2011 to December 2015. Tumor tissue sections were evaluated for TLS through hematoxylin-eosin (HE) staining. Two hundred patients receiving TACE treatment were divided into the TLS positive group and the TLS negative group. Propensity score matching (PSM) was used to reduce confounding factors. Kaplan-Meier survival curves, log-rank tests and Cox proportional hazards model were employed to assess the impact of TLS on prognosis of patients receiving postoperative adjuvant TACE. ResultsBefore PSM, the TLS positive group (n＝101) had significantly longer early recurrence-free survival (RFS) and overall survival (OS) compared to TLS negative group (n＝99, P＜0.001). After PSM, there were 69 cases in both the TLS positive and TLS negative groups, with no statistically significant differences in baseline data between the two groups. The TLS positive group still showed significantly longer early RFS (P＜0.001) and OS (P＝0.002). The results of the Cox proportional hazards model indicated that the presence of TLS in tumor tissue was an independent protective factor for early RFS (HR＝0.240, P＜0.001) and OS (HR＝0.282, P＜0.001) in patients undergoing postoperative adjuvant TACE treatment. Subgroup analysis of 345 patients showed that among patients with TLS present in tumor tissue, those receiving adjuvant TACE had longer early RFS (P＝0.034) and OS (P＝0.018) compared to those who did not receive adjuvant TACE, while the efficacy of adjuvant TACE was not significant in patients without TLS. ConclusionsTLS is an important indicator affecting the efficacy of postoperative adjuvant TACE and patient prognosis.